The Implementation of Transmigration Residents’ Placement in Creating an Independent Society in Ayumolingo Village, Pulubala District, Gorontalo Regency - Abdurahman Abdullah; Yosep Koton; Sudarsono (Journal of Economic, Business, and Administration (JEBA), 2021)
This study aims to determine the implementation of the placement of transmigration residents in realizing an independent society in Ayumolingo Village, Pulubala District, Gorontalo Regency and the factors that hinder the implementation of Transmigration Residents’ placement in creating an Independent Society in Ayumolingo Village, Pulubala District, and Gorontalo Regency. Research method used is a qualitative research method with data collection techniques including: 1) observation; 2) interview; and 3) documentation. Activities in data analysis, namely: 1) data reduction stage; 2) data presentation stage; and 3) data verification stage. The results in this study are the implementation of the placement of transmigration residents from planning has not been maximized because it does not include or involve residents around the transmigration area or area as required and the implementation is not optimal because it still causes social jealousy of local residents and complaints from transmigration residents because the land is determined/given by the government is not in accordance with what is in the location of the transmigration area and the supervision has not been effective, so that there are transmigration residents who have been placed away from their homes/settlement locations, so that the government’s goal in an effort to achieve business independence and make transmigration residents feel at home or settle in the location of the transmigration area has not can be realized. As for the factors that hinder the implementation of the placement of Transmigration Citizens in Ayumolingo Village, Pulubala District, Gorontalo Regency, namely commitment is still low, transparency is still lacking and human resources are still limited, both implementing apparatus resources and community resources, thus hampering the implementation and implementation placement of transmigrants.